Lucio phenomenon in pregnancy: A histopathology review - Oktavriana,, Triasari; Rosmarwati, Ervina; Novriana, Dita Eka; Mudigdo, Ambar; Fiqnasyani, Siti Efrida (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Lucio phenomenon (LP) is a reaction occurring in lepromatous, non-nodular, diffuse leprosypatients who have not received multidrug therapy (MDT). The diagnosis of LP are based on clinical features and supported by histopathological examination. This report was conducted to establish a diagnosis of LP byhistopathological examination, considering that cases of LP in pregnancy are quite rare so that clinicians can be more precise. Case: A 35-year-old pregnant woman complained of extensive ulcers on her hand and legs. Madarosis, saddle nose, and earlobes were found A slit skin smear examination showed a bacterial index of +4 and a morphological index of 20%. A skin biopsy from a leg ulcer with HE staining revealed thinning of the epidermis,foamy macrophages, inflammatory cell infiltrate in the dermis and subcutaneous layers, necrotizing vasculitis with thickening of blood vessel walls, and perivascular lymphohistiocytic infiltrate. Histopathological examination of auricular infiltrate showed basket weave type hyperkeratosis, grenz zone, lymphohistiocytic inflammatory cell infiltrates, foamy and touton cells. Histopathological examination by FF staining showed a heavy M. leprae invasion. Discussion: Histopathological characteristics of LP in this patient found flattened epidermis, subepidermal grenz zone, aggregates and sheets of foamy macrophages admixed with predominantly huge numbers of acid-fast bacilli, foamy macrophages and touton cells. The main microscopic features also found subcutis necrotizing vasculitis. Histopathological examinations are essential to diagnose LP. Conclusion: Histopatholgy of Lucio Phenomenon found grenz zone, inflammatory cell infiltrate and foamy cells. This histopatholgy will support the diagnosis and best treatment for LP patient.